Brand Co-Creation dalam Mengoptimalkan Pengaruh Social Media Merketing Terhadap Business Performance - Andriyanto, Muhamad; Nabhan, Faqih (Universitas Muhammadiyah Surakarta, 2025)
This study uses brand co-creation as a mediating variable to determine the effect of social media marketing on company performance. The population in this study were MSMEs in Salatiga City and used hair formula calculations to select 110 samples. The sample was obtained using purposive sampling. Data were collected using Google Form from MSME actors in Salatiga City. The analysis tool used was Partial Last Square (PLS) software. By using a Likert scale to measure respondent data, a questionnaire was created and sent to MSME actors in Salatiga City. The questionnaire was created and sent to MSME actors in Salatiga City to collect primary data for this study. The following findings were taken from the results of data processing using SmartPLS: Business performance is significantly and positively influenced by social media marketing; co-branding is significantly and positively influenced by social media marketing; and co-branding can mediate the positive and impactful relationship between social media marketing and business performance.